2021
DOI: 10.3389/fphys.2021.700220
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 in the Pathogenesis of Renal Abnormalities Observed in COVID-19 Patients

Abstract: Coronavirus disease 2019 (COVID-19) was first reported in late December 2019 in Wuhan, China. The etiological agent of this disease is severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and the high transmissibility of the virus led to its rapid global spread and a major pandemic (ongoing at the time of writing this review). The clinical manifestations of COVID-19 can vary widely from non-evident or minor symptoms to severe acute respiratory syndrome and multi-organ damage, causing death. Acute kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“…Based on previous studies demonstrating that SARS-CoV-2 binds to the ACE2 enzyme ( Jackson et al, 2021 ), it is possible to postulate that SARS-CoV-2/ACE2 binding might impairs the inactivation process of des-Arg 9 -BK, as ACE2 is well-known to degrade des-Arg 9 -BK ( Sodhi et al, 2018 ; Tabassum et al, 2022 ). In this aspect, it has been suggested that kidney injury caused by SARS-CoV-2 could also be due, at least in part, to the exacerbation of des-Arg 9 -BK/B1R axis effects ( Azinheira Nobrega Cruz et al, 2021 ), as it has been shown here. Thus, less des-Arg 9 -BK inactivation combined with its longer systemic blood half-life ( Cyr et al, 2001 ; Jackson et al, 2021 ) might partially explain the higher circulating levels of des-Arg 9 -BK in COVID-19 patients.…”
Section: Discussionsupporting
confidence: 57%
“…Based on previous studies demonstrating that SARS-CoV-2 binds to the ACE2 enzyme ( Jackson et al, 2021 ), it is possible to postulate that SARS-CoV-2/ACE2 binding might impairs the inactivation process of des-Arg 9 -BK, as ACE2 is well-known to degrade des-Arg 9 -BK ( Sodhi et al, 2018 ; Tabassum et al, 2022 ). In this aspect, it has been suggested that kidney injury caused by SARS-CoV-2 could also be due, at least in part, to the exacerbation of des-Arg 9 -BK/B1R axis effects ( Azinheira Nobrega Cruz et al, 2021 ), as it has been shown here. Thus, less des-Arg 9 -BK inactivation combined with its longer systemic blood half-life ( Cyr et al, 2001 ; Jackson et al, 2021 ) might partially explain the higher circulating levels of des-Arg 9 -BK in COVID-19 patients.…”
Section: Discussionsupporting
confidence: 57%
“…ACE2 is mainly present in the respiratory system and has also been found in gastrointestinal tract, heart, kidneys, and brain. 5–8 Thus, SARS-CoV-2 affects lungs as well as other organs and patients may die from multiorgan failure. 9 , 10 Kidney disease most commonly associated with SARS-CoV-2 infection is acute kidney injury (AKI) with histopathological alterations such as acute tubular necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Potential explanations for the kidney-related benefits of RAS inhibitors include the ability of ARBs to compete with SARS-CoV-2 for the binding to the ACE2 receptors found in proximal tubular cells (4). In addition, the increased production of angiotensin II seems to drive the occurrence of kidney injury, and RAS inhibitors could block the physiologic effect of angiotensin II (5). Therefore, we urge the performance of clinical trials to investigate the potential protective effects of RAS inhibitors against the development of acute kidney injury in patients with COVID-19.…”
mentioning
confidence: 99%
“…Accordingly, our overarching aim was to examine sex determinants of responses to ARBs and ACEis in acute COVID-19. Mechanisms of preferential ARBs' efficacy for AKI in males in acute COVID-19 could include greater renal injury in males due to direct severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-induced renal injury, lymphocyte infiltration, diffuse proximal tubule injury, and acute tubular necrosis (4,5). Postmortem renal tissue of COVID-19 patients with AKI shows viral particles in the kidney and SARS-CoV-2 nucleoprotein antigen accumulation in renal tubules (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation